Revision of Epyris afer (Magretti, 1884), comb. rev. (Hymenoptera: Bethylidae) with new synonymy and description of two new species - Stein, Paulo R. W.; Alencar, Isabel D. C. C.; Barbosa, Diego N.; Azevedo, Celso O. (Zootaxa, 2011)
Pristocera afra Magretti, 1884 which currently belongs to genus Epyris Westwood is revised and redescribed. The lectotype of P. afra Magretti is designated. New synonymy is proposed for Epyris afer (Magretti, 1884): Epyris pilosipes Kieffer, 1904, syn. nov.; Epyris analis Kieffer, 1905, syn. nov.; Epyris secundus Brues, 1906, syn. nov.; Epyris rugicollis Cameron, 1906, syn. nov.; Epyris plurilineata Turner, 1928, syn. nov. Two new species Epyris enerterus Stein & Azevedo, sp. nov. (Myanmar) and Epyris penatii Stein & Azevedo, sp. nov. (Sudan) are described and illustrated. Epyris afer (Magretti) is newly recorded from Yemen, United Arab Emirates, Thailand, and Vietnam.